The Influence of Light Irradiation on the Photocatalytic Degradation of Organic Pollutants - Enesca, Alexandru; Isac, Luminita (Materials, 2020)
The design of a photocatalytic process must consider intrinsic and extrinsic parameters affecting its overall efficiency. This study aims to outline the importance of balancing several factors, such as radiation source, total irradiance, photon flux, catalyst substrate, and pollutant type in order to optimize the photocatalytic efficiency. Titanium oxide was deposed by the doctor blade technique on three substrates (microscopic glass (G), flour-doped tin oxide (FTO), and aluminum (Al)), and the photocatalytic properties of the samples were tested on two pollutants (tartrazine (Tr) and acetamiprid (Apd)). Seven irradiation scenarios were tested using different ratios of UV-A, UV-B+ C, and Vis radiations. The results indicated that the presence of a conductive substrate and a suitable ratio of UV-A and Vis radiations could increase the photocatalytic efficiency of the samples. Higher efficiencies were obtained for the sample Ti_FTO (58.3% for Tr and 70.8% for Apd) and the sample Ti_Al (63.8% for Tr and 82.3% for Apd) using a mixture of three UV-A and one Vis sources (13.5 W/m2 and 41.85 µmol/(m2·s)). A kinetic evaluation revealed two different mechanisms of reaction: (a) a one-interval mechanism related to Apd removal by Ti_FTO, Ti_Al (scenarios 1, 4, 5, and 7), and Ti_G samples (scenario 7) and (b) a two-interval mechanism in all other cases.
Keywords: TiO2; doctor blade; photocatalysis; light spectra; photon flux; kinetics